Conductance studies on sodium silicates - Lee, C. K.; Dent Glasser, L. S. (Wiley, 1975)
Sodium silicate solutions with silicon dioxide: sodium monoxide mole ratios of 3.41 : 1 and 3.98 : 1 were dried to form gels. Some conductance studies were carried out on the sodium silicate as it dried, and when the dried material was heated up to 160 °C. The results suggest that conduction is mainly due to sodium ions both in the solution and in the gel; to this extent the mechanism of con, duction is similar to that in sodium silicate glasses. However, the gel has a much higher conductance than a glass of similar Na2O : SiO2 ratio, and this is probably because the gel contains hydroxyl ions and hydrated silicate ions, whereas the glass does not; moreover, the gel has a much less tightly packed structure than does the glass.